The Renewable Energy Production-Economic Development Nexus - Kazar, Gorkemli; Kazar, Altug (International Journal of Energy Economics and Policy, 2014)
As renewable energy requirements increases, its relation with development is controversial. In this study, by taking human development index for development level, the relationship between renewable electricity net generation values and development has been searched with panel analysis. Study covers two different time periods: 1980-2010 with 5 year data to analyze long term effects and 2005-2010 yearly data for short term effects. Unlike previous studies, energy generation has been taken into consideration for it is thought to be more related with economic development. It is found that in the long run economic development will be leading to renewable energy production, while in the short run there exists a bidirectional causal relationship between renewable energy production and economic development. In addition, the causal relationship between economic development and renewable energy production varies both in the long run and in the short run due to human development level of the countries. Keywords: renewable energy; Human Development Index; causality JEL Classifications: C10; N70; O150